Coping with stress: Exploring the lived experiences of English teachers who persist in Malaysian rural schools - Aziz, Ameiruel Azwan Ab; Swanto, Suyansah; Azhar, Sheik Badrul Hisham Jamil (Universitas Pendidikan Indonesia, 2019)
Teaching English as a second language is a long and complex undertaking, particularly when it is done in multilingual rural areas where English serves a limited purpose. The purpose of this phenomenological case study was to shed light and describe the lived experiences of ten English teachers who persist in rural schools in Sabah, Malaysia. Data gleaned from in-depth interviews and observations and were thematically analyzed. The research questions captured teachers' perceptions of the existing teaching and learning environment, sources of stress and coping strategies through interviews and observations. The findings depicted that rural schools do not benefit from a conducive environment to support English teaching and learning due to the limited English environment, shortage of teaching resources and poor physical environment. The findings also revealed that dealing with low English proficiency (LEP) students was their main stressor in teaching English in rural schools, followed by students' disruptive behaviours, excessive workload and lack of support. To cope with the stress, teachers first evaluate and assess possible solutions through a stress appraisal process. The present study identified that the personal, social, professional, and institutional coping strategies were used by teachers to cope with stress faced. The findings have implications for the teaching of English in rural schools and could offer recommendations for changes in educational practices in which the authorities, school administrators and teachers could collaborate in improving English education in rural schools and thus students' learning, achievement, and school reputation.